(untitled) - VUFO-NGO resource centre (Hanoi, 2008)
The document sought to be a resource providing information about the work organizations were conducting in the country, which activities they were involved in, and where they were working. This overall aim is still to: increase knowledge, in Vietnam and overseas, about INGOs working in Vietnam; and help foster communication among INGOs, the Government of Vietnam, local groups, organizations and associations, and other international and local agencies.
Keywords: International economic relations,Non-governmental organizations,Phi chính phủ,Các mối quan hệ kinh tế quốc tế; Directorries,Thư mục